Spectroscopic, thermogravimetric and structural characterization analyses for comparing Municipal Solid Waste composts and vermicomposts stability and maturity. (July 2017) - Soobhany, Nuhaa; Gunasee, Sanjana; Rago, Yogeshwari Pooja; Joyram, Hashita; Raghoo, Pravesh; Mohee, Romeela; Garg, Vinod Kumar
Highlights: Extensive comparison of maturity indexes among compost and vermicompost is assessed. Difference in intensity of peaks by FT-IR spectra between compost and vermicompost. Vermicompost TG curve had lower mass loss than compost, indicating higher stability. Low-temperature peak in vermicompost DSC curve proved greater maturity than control. SEM micrographs of vermicompost showed strong disaggregation compared to compost. Abstract: This is the first-ever study of its kind for an extensive assessment and comparison of maturity indexes between compost and vermicompost that have been derived from Municipal Solid Waste (MSW). The spectroscopic (Fourier transform infrared spectroscopy: FT-IR), thermogravimetric analysis (TG), differential scanning calorimetry (DSC) and structural characterization (scanning electron microscope: SEM) were recorded. FT-IR spectra showed an increase in conversion of polysaccharides species and aliphatic methylene groups in vermicompost compared to compost as depicted from the variation of the intensity of the peaks. TG curves of final vermicompost showed a much lower mass loss when compared to compost, indicating higher stability in feedstock. SEM micrographs of the vermicompost reflected strong fragmentation of material than composts which revealed the extent of intra-structural degradation of MSW. These findings elucidate on a clear comparison between composts and vermicomposts in terms of maturity indexes for soil enhancement and in agriculture as organic fertilizer.